2019
DOI: 10.1038/s41419-019-1467-7
|View full text |Cite
|
Sign up to set email alerts
|

NPTX2 promotes colorectal cancer growth and liver metastasis by the activation of the canonical Wnt/β-catenin pathway via FZD6

Abstract: Accumulating evidence from clinical and epidemiological studies has highlighted the close correlation between the individual risk of cancer and nervous system diseases. The expression of neuronal pentraxin 2 (NPTX2) is absent in Alzheimer’s disease, anxiety, and depression. Herein, we found that NPTX2 mRNA and protein expression was significantly upregulated in colorectal carcinoma (CRC). NPTX2 expression level gradually increased with CRC progression and was closely associated with poor prognosis. In vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 34 publications
(33 reference statements)
1
42
0
Order By: Relevance
“…Actually, previous studies indicated that HSPA1A [18,19], UNC5C [20,21], CBFA2T3 [22,23], NPTX2 [24,25], EPHX4 [26], and AQP1 [27][28][29] have been reported to be associated with CRC. This result also suggested the feasibility of our present results.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, previous studies indicated that HSPA1A [18,19], UNC5C [20,21], CBFA2T3 [22,23], NPTX2 [24,25], EPHX4 [26], and AQP1 [27][28][29] have been reported to be associated with CRC. This result also suggested the feasibility of our present results.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal pentraxin 2 ( NPTX2 ) is a member of the neuronal pentraxin family and is essential for the formation of synapsis. NPTX2 was found overexpressed at both mRNA and protein level in CRC, particularly in metastatic lesions [ 29 ]. NPTX2 , which was found to positively correlate with tumour stages, lymphatic invasion, distant metastasis, and poor patients’ outcome, promotes β-catenin nuclear translocation and the expression of c-myc , cyclin D1, Snail , and N-cadherin .…”
Section: Canonical Wnt/β-catenin Pathway and Crcmentioning
confidence: 99%
“…No NPTX2 receptors have been identified in CRC; however, its cellular internalization was found mediated by the Wnt/β-catenin receptor, FZD6 . Additionally, it has been reported that NPTX2/FZD6 interaction translates in cancer cell proliferation and metastasis formation by triggering the Wnt/β-catenin pathway [ 29 ] ( Table 1 ).…”
Section: Canonical Wnt/β-catenin Pathway and Crcmentioning
confidence: 99%
“…The siRNAs for TLRs (TLR1-10) were purchased from GenePharma (Shanghai GenePharma Co., Ltd., Shanghai, China). Table S1 displays the sequences, and the experimental method was performed as previously described (15).…”
Section: Small Interfering Rna Transfectionmentioning
confidence: 99%